Occupational exposure, attitude to HIV-positive patients and uptake of HIV counselling and testing among health care workers in a tertiary hospital in Nigeria - Modupe O. Onadeko; Mary O. Balogun; Olanrewaju O. Onigbogi; Folashade O. Omokhodion (Taylor & Francis Group, 2017)
Health care workers (HCWs) are at risk of occupational exposure to HIV. Their attitude to HIV-positive patients influences patients' willingness and ability to access quality care. HIV counselling and testing (HCT) services are available to inform HCWs and patients about their status. There is little information about HCT uptake and attitude to HIV-positive patients among HCWs in tertiary health facilities in Nigeria. The aim of this study was to determine occupational exposure and attitude to HIV-positive patients and level of uptake of HCT services among HCWs in a tertiary hospital in Nigeria. A cross-sectional design was utilized. A total of 977 HCWs were surveyed using semi-structured, self-administered questionnaires. Nurses and doctors comprised 78.2% of the respondents. Their mean age was 35 ± 8.4 years. Almost half, 47.0%, reported accidental exposure to blood and body fluids (BBFs) in the preceding year. The main predictor of accidental exposure to BBFs in the last year was working in a surgical department, OR = 1.7, 95% CI (1.1-2.6). HCWs aged <40 years, OR = 5.5, 95% CI (1.9-15.9), who had worked for >5 years, OR = 3.6, 95% CI (1.4-9.3) and who work in nursing department, OR = 6.8, 95% CI (1.7-27.1) were more likely to be exposed to BBFs. Almost half, 52.9%, had accessed HCT services. Predictors for HCT uptake were age <40 years OR = 1.6, 95% CI (1.1-2.4), having worked for >5 years OR = 1.5, 95% CI (1.03-2.2) and working in medical department OR = 1.7, 95% CI (1.1-2.8). Respondents in nursing departments were more likely to require routine HIV test for all patients, OR = 3.9, 95% CI (2.4-6.2). HCWs in the laboratory departments were more likely to believe that HIV patients should be on separate wards, OR = 3.6, 95% CI (1.9-7.0). HCWs should be protected and encouraged to access HCT services in order to be effective role models in the prevention of HIV/AIDS.